Kadar Low Density Lipoprotein dan Gambaran Histopatologi Hepar pada Tikus Model Diabetes Mellitus Tipe 1 dengan Pemberian Ekstrak Etanol Curcuma longa L - Herlina Pratiwi; Djoko Winarso; Nunung Handoyo (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2016)
This study was conducted to determine levels of LDL and liver damage in rats (Rattus norvegicus) models of type 1 diabetes mellitus inducted by streptozotocin (STZ) with etanol extract of turmeric (Curcuma Longa L) therapy. Animals used rat (Rattus norvegicus) 3-month-old males who were divided into 5 groups, each group consisting of four mice. The group was divided according to treatment: negative control (not induced by STZ), the positive control group (STZ induced), groups of rats DM 1 with etanol turmeric extract therapy a dose of 1.2 g / kg, groups of rats DM 1 with etanol turmeric extract therapy a dose of 1.8 g / kg, and groups of rats DM 1 with etanol turmeric extract therapy a dose of 2.7 g / kg. LDL levels measured by direct method and the severity of liver damage was observed through histopatology picture. The results showed that the etanol extract of turmeric dose of 2.7 g / kg in a rats model of type 1 diabetes mellitus can lower LDL levels up to 59.55%, and reduced the severity of fatty liver with reduced fat vacuoles. The conclusion from this study that the etanol extract of turmeric contains antioxidants that can lower LDL levels and reduced the severity of fatty liver in type 1 diabetes mellitus.